To complete the square for the quadratic function \( y = x^2 - 16x + 14 \), we can follow these steps:
-
Group the x terms: \[ y = (x^2 - 16x) + 14 \]
-
Complete the square:
- We take the coefficient of \( x \) (which is -16), divide it by 2, and square it: \[ \left(\frac{-16}{2}\right)^2 = (-8)^2 = 64 \]
- Add and subtract this value inside the parentheses: \[ y = (x^2 - 16x + 64 - 64) + 14 \]
- Now rewrite the equation: \[ y = (x - 8)^2 - 64 + 14 \]
-
Simplify: \[ y = (x - 8)^2 - 50 \]
Now, we can see that the equation of the parabola in vertex form is: \[ y = (x - 8)^2 - 50 \] From this, we can identify the vertex as: \[ (8, -50) \]
Thus, the vertex of the function \( y = x^2 - 16x + 14 \) is \((8, -50)\).
The correct response is: (8, -50).